PENGARUH SOSIALISASI ORGANISASI PADA KOMITMEN AFEKTIF YANG DIMEDIASI OLEH KESESUAIAN NILAI - Stefanus Rumangkit (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2016)
This study developed a research framework for the understanding of organizational socialization and affective commitment at the individual level by using the self-assessment (self-report). This study aimed to examine the effect of organizational socialization on affective commitment to the suitability of the variable pemediasi. Data collected as many as 135 respondents were obtained from educative and administrative employees who work at Sanata Dharma University, Yogyakarta. From the data obtained, the data analysis using regression model pemediasi through a simple regression analysis and regression.The results of this study indicate that organizational socialization positive and significant effect on affective commitment. From the results of this study can be reported that the organizational socialization positive and significant effect on the suitability value. Other findings from this study indicate that the suitability of the positive and significant effect on affective commitment. In addition, the results of this study also showed that the suitability of the mediating effect of organizational socialization on affective commitment.Keywords: organizational socialization, affective commitment, socializing influence on affective commitment, the suitability of the